Development of learning skills in university students - África María Cámara Estrella; Elena Mª Díaz Pareja; Juana Mª Ortega Tudela (Universitat Politècnica de València, 2015)
The  incorporation  of  Spain  into  the European Higher Education Area (EHEA) is  changing  the  traditional  approach to Higher Education; thus, the focus is now on Learning with teaching being expected to develop skills and use active methodologies.  Despite  this,  faculties still use traditional methodologies based on the simple idea of transmission of knowledge and, unfortunately, pay little attention  to  student's  active  learning and methodological innovations. In the present work we explore the potential benefits of the Problem-Based Learning (PBL) methodology as a teaching strategy for future teachers training. Specifically, we  developed  a  teaching  innovation project in which we implemented such a methodology in the Grades of Elementary Education and Early Childhood Education. The results show that PBL increases students'  motivation,  improves  self-learning skills, and facilitates teamwork, problem solving and new knowledge learning.  In  addition,  PBL  provides students with the opportunity to develop the social dimension of integral education through the education in values and the ethical commitment involved in sharing knowledge and learning.